Passivation of Interfaces in Thin Film Solar Cells: Understanding the Effects of a Nanostructured Rear Point Contact Layer. Issue 2 (5th December 2017) - Salomé, Pedro M. P.; Vermang, Bart; Ribeiro‐Andrade, Rodrigo; Teixeira, Jennifer P.; Cunha, José M. V.; Mendes, Manuel J.; Haque, Sirazul; Borme, Jêrome; Águas, Hugo; Fortunato, Elvira; Martins, Rodrigo; González, Juan C.; et al.
Abstract: Thin film solar cells based in Cu(In, Ga)Se2 (CIGS) are among the most efficient polycrystalline solar cells, surpassing CdTe and even polycrystalline silicon solar cells. For further developments, the CIGS technology has to start incorporating different solar cell architectures and strategies that allow for very low interface recombination. In this work, ultrathin 350 nm CIGS solar cells with a rear interface passivation strategy are studied and characterized. The rear passivation is achieved using an Al2 O3 nanopatterned point structure. Using the cell results, photoluminescence measurements, and detailed optical simulations based on the experimental results, it is shown that by including the nanopatterned point contact structure, the interface defect concentration lowers, which ultimately leads to an increase of solar cell electrical performance mostly by increase of the open circuit voltage. Gains to the short circuit current are distributed between an increased rear optical reflection and also due to electrical effects. The approach of mixing several techniques allows us to make a discussion considering the different passivation gains, which has not been done in detail in previous works. A solar cell with a nanopatterned rear contact and a 350 nm thick CIGS absorber provides an average power conversion efficiency close to 10%. Abstract : In this work ultrathin 350 nm Cu(In, Ga)Se2 (CIGS) solar cells with passivated rear contact are studied and characterized. The rear interface passivation is achieved using an Al2 O3 nanopatterned point structure and an average power conversion efficiency close to 10% is achieved due to chemical passivation and increased light trapping.